pH AS A FACTOR INFLUENCING MATURATION OF PENAEUS INDICUS IN CAPTIVITY - Muthu, M S; Laxminarayana, A; Mohamed, K H (Indian Journal of Fisheries, 2011)
Unilaterally eye-ablated females of Pgnaeus indicus have matured andspawned in 3-4 days time when the pH of the maturation pools was maintainedat a level similar to that of the sea, between 8.0 and 8.2, by daily addition ofsodium carbonate. But eye-ablated females kept in pools where the pH was allowedto fall below 7.9 did not attain full ovarian development and no spawning wasobtained.